The Effect of Metal Mixture Composition on Stress Values when Metal Joints are Exposed to Heat - نصره مهند (Latakia University Journal -Engineering Sciences Series, 2021)
This research presents a study of the effect of the type of alloy metal girders used in metal connections, as well as the effect of the type of sheet metal alloy that fix the girders together with the presence of bolts at high temperatures (fire conditions), by using the CATIA V5 program techniques to simulate the loading and failure process and calculate the stresses generated in Each case studied down to the best type of mineral alloy that gives the best strength and the least stress, The calculated stresses are known in computer design programs as von-mises stress and were calculated for each case at different temperatures, from the medium temperature to the melting points of the material at the time when all other parameters affecting the stresses generated for the junction were fixed in order to obtain. A thorough understanding of the influence of the type of mixture The studied fittings were of IPE 240 type, consisting of eight screws with a diameter of 22 mm and a plate thickness of 15 mm, with reinforcing joints of 30 mm thickness and a pitch angle of 50 °.